Thermoelectrical properties of silicon substrates with nanopores synthesized by metal-assisted chemical etching - Li, Yijie; Toan, Nguyen Van; Wang, Zhuqing; Samat, Khairul Fadzli; Ono, Takahito (Institute of Physics Publishing, 2020)
A silicon substrate consisting of nanoporous silicon film could enhance the thermoelectric performance of bulk silicon due to its low thermal conductivity. Metal-assisted chemical etching (MACE) is a wet method for fabricating diverse nano/micro structures, which uses a noble metal as the catalyst for etching of semiconductor materials. In this study, we report the thermoelectrical properties of silicon substrates with nanopores in different porosities fabricated by MACE employing Ag nanoparticle as a metal catalyst. Different porosities of the nanoporous silicon layer were obtained by adjusting the deposition time of Ag nanoparticles. The lateral nanopores were found on the surface of the vertical nanopores sidewall caused by Ag nanoparticles. With the increase of the porosity, the surface area of the nanopores sidewall became rougher. In comparison with single-crystal silicon, silicon substrates with nanopores can enhance the thermoelectric figure of merit, ZT, due to the relativity high Seebeck coefficient and low thermal conductivity. However, lower electrical conductivity limits the enhancement of the ZT value. The porosity effect on the thermoelectrical properties of silicon substrates with nanopores was evaluated. The Seebeck coefficient has a maximum value at a porosity of 38% and then decreases at a porosity of 49%, and the electrical conductivity and thermal conductivity decrease with the increase of porosity. At a porosity of 38%, the ZT value of silicon substrates with nanopores can reach approximately 0.02, which is 7.3 times larger than that of the original high-doped single-crystalline silicon. Thus the nanoporous silicon film fabricated by MACE can enhance the thermoelectric performance of the bulk silicon.